Further Considerations for the Analysis of ENF Data for Forensic Audio and Video Applications - Cooper, Alan J. (International Journal of Speech, Language and the Law, 2011)
The Electric Network Frequency (ENF) Criterion is becoming an established forensic analysis tool for determining the originating date and time of a recording and helping to authenticate digital audio and video evidence. To date, proposed comparison metrics for an automated approach have been based on variants of the mean squared error or the correlation coefficient. These algorithms are discussed and empirically compared in the context of ENF pattern matching. The operation of an electrical network under normal and adverse operating conditions is considered in relation to ENF behaviour, and the possible relationships between a network’s ENF dynamics and a networks identity are discussed. This article compliments one previous by the author relating to the theory and practice in the use of an automated approach to the ENF Criterion.